ANALYSIS ON LOAD CARRIAGE VIBRATION OF CONVENTIONAL RAIL ENDLESS ROPE DRIVEN TRANSPORT SYSTEM - WANG JinLi (Jixie qiangdu)
The load carriage is an important part of the conventional rail endless rope driven transport system aiming at the safety accidents such as derailment,descent and rollover caused by the vibration of the carriage in the process of transporting people or goods. In this paper,the vibration of the load carriage of the standard wheeling device and the clamp wheeling device are tested under three conditions: straight lanes,horizontal turning radius of 9 m,and vertical turning radius of 15 m. The analysis of the vibration performance of different gear trains under a variety of operating speeds shows that the clamp wheeling device has the best stability. With the increase of speed,when the running speed is more than 2. 0 m/s,the lateral amplitude of the standard wheeling device is larger; when the running speed is more than 1. 5 m/s,the longitudinal amplitude and the lateral amplitude of the standard wheeling device are larger than that of the clamp rail gear train,It is recommended to add the guard rail device; the running speed should not exceed 1. 8 m/s during vertical turning operation.